AN ACCURATE MODULATION CLASSIFICATION ALGORITHM FOR MULTIPLE-INPUT MULTIPLE-OUTPUT WIRELESS SYSTEMS - RIDA , MOHAMMAD BAHLOUL (2015)
Automatic Modulation Classification (AMC) is a very important process for any receiver that has a limited or no prior knowledge of the received signals. It is important for many areas such as interference identification, software radio and for many other civilian and military applications. Even though intense researches have been carried out in the field ofAMC during the last decades, most ofthem were mainly conducted for Single-Input Single-Output (SISO) systems. Recently, Multiple-Input Multiple-Output (MIMO) techniques have attracted much attention and gained more popularity, where multiple transmit and receive antennas are used to enhance the data rate and/or robustness of the wireless link. However, the transmission over multiple antennas makes the AMC problem more challenging due to the mutual interference introduced by the MIMO channel.